One year follow up of a child with clinico-radiologically diagnosed left Thalomopeduncular Glioma - Emmanuel Garba Sunday; Eno-Abasi Garba Sunday; Alvan-Emeka K. Ukachukwu; Nourou Dine Adeniran Bankole (Romanian Neurosurgery)
Background Absence of or poor facility and equipment have been the bane of management of thalamic tumours in low-resource settings.